PROFILE OF PROSPECTIVE TEACHERS' MATHEMATICAL COMMUNICATION ABILITY REVIEWED FROM ADVERSITY QUOTIENT - Muhtarom Muhtarom; Adelia Dian Pratiwi; Yanuar Hery Murtianto (Jurnal Infinity, 2021)
Communication skills are an essential aspect that students need to possess by students who want to succeed in their studies, where students' mathematical communication can organize mathematical thinking both orally and in writing. While AQ is intelligent in facing difficulties, a student must face the problems that exist in them. This study aims to determine the profile of prospective mathematics prospective teacher's mathematical communication skills in terms of adversity quotient. This study was conducted on mathematics education students in the 6th semester of Universitas PGRI Semarang. This research is a descriptive qualitative study. Subjects taken from 57 respondents were three students in the category of climbers, campers, and quitters. Written tests and interviews do data collection. Indicators of mathematical communication skills used in this study include drawing, writing, and mathematical expression. The results showed that the subject climber can meet all the indicators of mathematical communication skills and can be said to be good. Subject campers tend to meet all indicators of mathematical communication skills, have the power of communication in indicators drawing, and be quite useful. Quitter's subject tends not to meet all the communication indicators. The subject does not answer the drawing indicator's problem, and the writing and mathematical expression indicators are still wrong.